2022
DOI: 10.1021/jacs.1c11667
|View full text |Cite
|
Sign up to set email alerts
|

High Triplet Energy Iridium(III) Isocyanoborato Complex for Photochemical Upconversion, Photoredox and Energy Transfer Catalysis

Abstract: Cyclometalated Ir(III) complexes are often chosen as catalysts for challenging photoredox and triplet−triplet-energy-transfer (TTET) catalyzed reactions, and they are of interest for upconversion into the ultraviolet spectral range. However, the triplet energies of commonly employed Ir(III) photosensitizers are typically limited to values around 2.5−2.75 eV. Here, we report on a new Ir(III) luminophore, with an unusually high triplet energy near 3.0 eV owing to the modification of a previously reported Ir(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 174 publications
(338 reference statements)
2
61
0
4
Order By: Relevance
“…Metal-to-ligand charge-transfer (MLCT) excited states play a key role in many coordination complexes and organometallic compounds because they enable a range of different applications in photophysics and photochemistry. Precious and rare elements such as ruthenium(II), 1 500 osmium(II), 5 9 rhenium(I), 10 18 or iridium(III) 15 , 19 25 in polypyridine or cyclometalating coordination environments often feature a long-lived MLCT excited state, 26 , 27 whereas among first-row d 6 transition metal elements, this is yet a very rare occurrence. Iron(II) is by far most investigated in this regard, 28 − 44 yet only a handful of iron(II) complexes with MLCT lifetimes in the nanosecond time regime are known.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-to-ligand charge-transfer (MLCT) excited states play a key role in many coordination complexes and organometallic compounds because they enable a range of different applications in photophysics and photochemistry. Precious and rare elements such as ruthenium(II), 1 500 osmium(II), 5 9 rhenium(I), 10 18 or iridium(III) 15 , 19 25 in polypyridine or cyclometalating coordination environments often feature a long-lived MLCT excited state, 26 , 27 whereas among first-row d 6 transition metal elements, this is yet a very rare occurrence. Iron(II) is by far most investigated in this regard, 28 − 44 yet only a handful of iron(II) complexes with MLCT lifetimes in the nanosecond time regime are known.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Nevertheless, the triplet energy level ( E T ) of 64 kcal mol −1 has represented a plateau until very recent advances for iridium systems. 27 In addition to this limitation, the cationic nature of iridium complexes and the corresponding low solubility in many organic solvents often prevents the use of first choice sustainable solvents for catalytic reactions. 28 In the context of solvent compatibility, the exact amount required to enable catalysis is oftentimes overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…44 Most recently, Wenger et al have boronated heteroleptic Ru(II) and Ir(III) diimine complexes and demonstrated their high activity for energy transfer and photoredox catalysis. 45,46 Studies of cyanometallates have been driven by the promise of applications in magnetic materials involving single-molecule/Prussian-Blue analogues and in electrode materials for solid-state batteries. 18,[47][48][49] Of direct relevance to our research is the performance of reversible cyanometallates as electrolytes in redox flow batteries.…”
Section: N-methylpyrrolidinonementioning
confidence: 99%